Experimental evaluation of pharmacokinetic profile and biological effect of a novel paclitaxel microcrystalline balloon coating in the iliofemoral territory of swine. Issue 2 (23rd October 2013) - Buszman, Piotr P.; Milewski, Krzysztof; Żurakowski, Aleksander; Pajak, Jacek; Jelonek, Michał; Gasior, Paweł; Peppas, Athanasios; Tellez, Armando; Granada, Juan F.; Buszman, Paweł E.
Background New paclitaxel coated balloons (PCB) developments have been proposed to maintain therapeutic levels of drug in the tissue while decreasing particle release. In this series of studies, we evaluated the pharmacokinetic profile and biological effects after paclitaxel delivery via novel microcrystalline PCB coating (mcPCB, Pax®, Balton) in porcine iliofemoral arteries. Methods: Ten domestic swine were enrolled yielding 24 iliofemoral segments for evaluation. In the pharmacokinetic study, nine mcPCBs were dilated for 60 sec and animals sacrificed after 1 hr, 3 and 7 days. Studied segments were harvested and tissue paclitaxel concentration was analyzed utilizing HPLC. In the biological response evaluation, self‐expandable stents were implanted followed by post dilation with either mcPCB (n = 10) or POBA (n = 5). After 28 days, angiography was performed, animals were sacrificed and stented segments harvested for histopathological evaluation. Results: The 1‐hr, 3 and 7 days vessel paclitaxel concentrations were 152.9 ± 154.5, 36.5 ± 49.5, and 0.9 ± 0.7 ng/mg respectively. In the biological response study, stents in the mcPCB group presented lower angiographic measures of neointimal hyperplasia as expressed by late loss when compared to POBA (−0.43 ± 0.9 vs. 0.23 ± 1.2; P = 0.24) at 28 days. In the histopathological evaluation, percent area of stenosis (%AS) was reduced by 42% in the mcPCB group (P < 0.05). The healing process in mcPCB group was comparable to POBA with regard to fibrin deposition (0.7 vs. 0.7; P = ns), neointimal maturity (1.97 vs. 1.93; P = ns), inflammation score (0.92 vs. 1; P = ns) and endothelialization score (1.77 vs. 1.73; P = ns). The mcPCB group did however display a greater tendency of medial cell loss and mineralization (60% vs. 0; P = 0.08). Conclusions: Delivery of paclitaxel via a novel mcPCB resulted in low long‐term tissue retention of paclitaxel. However, this technological approach displayed reduced neointimal proliferation and favorable healing profile. © 2013 Wiley Periodicals, Inc.